Deciphering the role of (anti)aromaticity in cofacial excimers of linear acenes. (26th September 2022) - Krishnan, Akhilesh; Diaz‐Andres, Aitor; Sudhakaran, Keerthy P.; John, Athira T.; Hariharan, Mahesh; Casanova, David
Abstract: Excited state aromaticity is a stimulating area of research, widely used as a probe to describe and rationalize many photochemical phenomena. Herein, we review some of the recent findings of unprecedented aromatic stabilization in spin singlet excimer and through‐space aromatic character in triplet excimers of a series of linear [n]acenes, as paramount examples of polycyclic aromatic hydrocarbons (PAHs). This review also provides insights on the aromatic stabilization profile of singlet benzene excimer formation, which can be related to antiaromaticity alleviation of the molecular (localized) S1 through exciton delocalization. The theoretical investigation of excimer stabilization using magnetic, electronic, and geometric aromatic indices manifested the presence of through‐space ring current in triplet cofacial excimers. The antiaromaticity of the sandwich (D6h ) spin singlet and triplet benzene excimers was also investigated by decomposing the excimer wave function as a linear combination of local exciton (LE) and charge transfer (CT) diabats and by identifying the contribution of these terms to the nucleus independent chemical shift (NICS) of the two 6‐membered rings. These results provide a detailed description of the unique (anti)aromatic properties in PAH excimers, establishing strong connection between this important chemical concept and the electronic structure intricacies of excimers. Abstract : Excimer formation relates to antiaromaticity alleviation of localized states via exciton delocalization, with the appearance of through space ring currents.